Problems Encountered by Grade 12 HUMSS Students on the Utilization of Cyber Space: Towards Comfort Cyber Wellness in Bestlink College of the Philippines S.Y.2021-2022: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Cyber Space or social network platforms is part of adolescents’ social life; because of COVID-19, education has become online. Moreover, people focus more on social media without knowing there is a risk in using social network platforms. This study has pointed out the impact of excessive use of social media. The study may be able to determine the effects of social media on the Grade 12 HUMSS students of Bestlink College of the Philippines. This study used descriptive research design to describe and determine the Problems Encountered by Grade 12 HUMSS Students on the Utilization of Cyber Space: Towards a Comfort Cyber Wellness in Bestlink College of the Philippines S.Y. 2021-2022. Simple Random sampling was used to select participants, and an online questionnaire was used as the research instrument for data collection. The primary purpose of this study is to examine the Problems Encountered by Grade 12 HUMSS Students on the Utilization of Cyber Space: Towards a Comfort Cyber Wellness in Bestlink College of the Philippines S.Y. 2021-2022. Earlier research shows that some students experienced cyber bullying, got false information, trolling, saw explicit videos and plagiarised on social media. The results reveal that most students are reading mean words from their bashers. In addition, they also experience things such as social anxiety due to cyberbullying. Undeniably, in some ways, the excessive use of social media can affect the lives of grade 12 HUMSS students of Bestlink College of the Philippines.
Keywords: HUMSS; BCP; cyberspace; cyber wellness; utilization